A novel subsurface sediment plate method for quantifying sediment accumulation and erosion in seagrass meadows - Ewers Lewis, Carolyn J.; McGlathery, Karen J. (Frontiers in Marine Science, 2023)
Sediment dynamics in seagrass meadows are key determinants of carbon sequestration and storage, surface elevation, and resilience and recovery from disturbance. However, current methods for measuring sediment accumulation are limited. For example, 210Pb dating, the most popular tool for quantifying sediment accretion rates over decadal timescales, relies on assumptions often at odds with seagrass meadows. Here, we have developed a novel subsurface sediment plate method to detect changes in sediment accumulation and erosion in real time that: 1) is affordable and simple to implement, 2) can quantify short-term (weeks to months) sediment dynamics of accumulation and erosion, 3) is non-destructive and minimizes impacts to surface-level processes, and 4) can quantify long-term (years) net sediment accumulation rates. We deployed subsurface sediment plates at two sites within a 20 km2 seagrass meadow in the Virginia Coast Reserve Long-Term Ecological Research site, USA. Here, we discuss spatial and temporal trends in sediment dynamics over a 25-month period, the sediment accretion rates estimated using the subsurface sediment plate method compared to previous estimates based on 210Pb dating, the precision of the method, and our recommendations for implementing the method for measuring surface sediment dynamics in other seagrass settings. We recommend the application of this method for quantifying short- and long-term changes in seagrass surface sediments across various spatial scales to improve our understanding of disturbance, recovery, restoration, carbon cycling, sediment budgets, and the response of seagrasses to rising sea levels.